Bladder cancer in Saudi Arabia: a registry-based nationwide descriptive epidemiological and survival analysis - Mohammad Ali Alghafees; Meshari A. Alqahtani; Ziyad F. Musalli; Ahmed Alasker (Annals of Saudi Medicine)
BACKGROUND: Our understanding of the risk factors, prevalence, incidence rate, and age distribution of bladder cancer (BC) in Saudi Arabia is insufficient due to limited data. OBJECTIVE: Describe the epidemiology and analyze factors associated with survival in patients with BC in Saudi Arabia. DESIGN: Retrospective medical record review. SETTINGS: Registry-based nationwide study. PATIENTS AND METHODS: The study included all records in the Saudi Cancer Registry of patients diagnosed with a primary BC from 1 January 2008 to 31 December 2017. Collected data included year of diagnosis, gender, age, marital status, region and nationality, tumor site of origin, tumor histological subtype, tumor behavior, tumor grade, tumor extent, tumor laterality, the basis of the diagnosis, and survival status. Factors predicting survival were tested by a Kaplan-Meier and Cox proportional hazards regression analysis. MAIN OUTCOME MEASURES: Mortality status on last contact. SAMPLE SIZE: 3750 patients. RESULTS: The overall incidence of BC was 1.4 per 100 000 persons. Significant differences in the distribution of survival were observed by age, gender, nationality, place of residency, tumor morphology, tumor grade and extension. The adjusted predictors of decreased survival were age, squamous cell carcinoma, Grade III and IV bladder tumors, regional direct extension, regional lymph node extension, combined regional lymph node and direct extension, and distant metastasis. Male gender and being widowed were predictors of improved survival in the unadjusted analysis. CONCLUSION: This study provides further understanding of BC in a region with a high prevalence of risk factorsuch as smoking. Highlighting these factors, specifically in Saudi Arabia, improves evidence-based practice in this region and may facilitate appropriate care to optimize outcomes. LIMITATIONS: Retrospective study and underreporting. CONFLICT OF INTEREST: None.